PENGARUH PERBANDINGAN TEPUNG SUWEG (Amorphophallus campanulatus) DAN TEPUNG KACANG HIJAU (Vigna radiate) TERHADAP KARAKTERISTIK COOKIES - Waisnawi, Putu Ayu Gaudiya; Yusasrini, Ni Luh Ari; Ina, Putu Timur (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 1 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i01.p06, 2019)
The purpose of this study was to determine the ratio effect of suweg flour and mung bean flour to produce the best characteristics of cookies. The Completely Randomized Design was used in this study with a comparison of suweg flour with mung bean flour consisting of 5 levels: 90%: 10%; 80%: 20%; 70%: 30%; 60%: 40%; 50%: 50%  The treatment was repeated 3 times for obtain 15 experimental units. Comparison of suweg flour and mung bean flour has a highly significant effect on fat content and crude fiber content and has a significant effect on protein content and carbohydrate levels of cookies. The comparison ratio of 60% suweg flour and 40% mung bean flour produces cookies with the best characteristics, namely: 1.37% moisture content, 2.29% ash content, 24.44% fat content, 8.89% protein content, carbohydrate content 63.01%, crude fiber content 21.78%, color, aroma , texture crispy, preference and overall acceptance were liked.